Elaboração de diagnósticos ambientais com apoio de imagens de radar Sentinel-1: uma proposta de ensino-aprendizagem para cursos superiores relacionados ao meio ambiente - Dias, Jean Carlos (2020)
This work presents a teaching-learning proposal aiming at environmental diagnostics with support of Sentinel-1 Radar images intended to under graduate students and recent graduates of higher courses of Environmental areas. This teaching-learning proposal is based on the Constructive Alignment, implements the Inverted Classroom model, is associated with Project-Based Learning, and places students at the center of the process, promoting active learning. It is also devoted to qualify the target audience with basic concepts of Sentinel-1 image processing and interpretation to enable diagnostics on widespread and important topics, such as deforestation, river mining and flooded areas, whose preprocessing, processing and image interpretation techniques can be replicated in other contexts. To evaluate the advantages and limitations of such teaching-learning proposal, as well as to verify the individual ability developed by students, an application was performed by means of a short course during 40 hours. The results observed attest that students were able to identify, process and interpret Sentinel-1 Radar images using the Sentinel Application Platform (SNAP) software, solving the proposed problems. This teaching-learning proposal was synthesized in a "Introduction Course to Sentinel-1 Image Processing and Interpretation", organized as a didactic guide for teachers. This resulting educational product has undergone two evaluations: the first, carried out by teachers, masters and doctors of the related area allowed them to concluded that, besides being relevant and appropriate, this course is easy to understand and to replicate in different educational contexts. The second one, carried out with students, was aimed at observing if they were capable to learn themselves basic notions of Sentinel-1 Radar image processing and interpretation. Although the proposal was designed to be applied by teachers, such evaluation helped us to enhance the perceptions regarding the product. Therefore, it was verified that students were capable to learn basic notions of Sentinel-1 image processing and interpretation and that the teachers-evaluators asserted to be capable to carry out such course themselves, there are supporting evidences that this educational product meets its purpose and that can be replicated in high level courses related to the Environmental areas.